Implementation of the Merrdeka Curriculum in Overcoming Bullying Through a Project to Strengthen the Profile of Pancasila : Implementasi Kurikulum Merrdeka Dalam Mengatasi Perundungan Melalui Projek Penguatan Profil Pelajar Pancasila - Fadilah, Aisyah Nurul; Hadi , Muhammad Fazlurrahman (Madrosatuna: Journal of Islamic Elementary School, 2024)
A Merrdeka Curriculum was one of the efforts to overcome educational problems that are currently hampering the learning process and development of students. The problem identified in this research was bullying that was rife in the school environment where this problem had many negative impacts on students such a decreased achievement, changes in bad behavior, hindering the learning process and so on. The purpose of this research obtained data and facts regarding the implementation of the Merrdeka curriculum that had been implementation in overcoming bullying through the project of strengthening the profile of Pancasila student. This research used qualitative research with a descriptive qualitative approach, data collction techniques using observation, interviews and documentation. The result showed that the implementation of the Merrdeka curriculum had been implemented was able to bring relevant impacts and changes, this was shown by the easy and deep learning process and minimal bullying problems. Through the project of strengthening the profile of Pancasila student realized by schools and teachers are able to bring students be able to understand what talents and interests they have so that students can develop their interests and talents, be able to achieve targets or goals that have been designed by the school and minimal bullying occurs.